Implementing evidence-based practices for urinary leakage prevention in ICU patients with indwelling catheters: A JBI-guided baseline review - Hong Bian; Zhiyin Zhou; Jingjing Yan; Zhengyu Yang; Ping Yu (PLoS ONE, 2026)
Objective To develop evidence-based audit indicators for urinary leakage prevention and management in ICU patients with indwelling catheters, to evaluate current clinical compliance with these indicators, and to analyze barriers and facilitators for evidence implementation using the JBI Clinical Evidence Application Model as a theoretical framework. Methods Using the Clinical Evidence Application Model from the Joanna Briggs Institute(JBI)Centre for Evidence in Healthcare in Australia as the theoretical framework,clinical nursing issues were identified.Literature searches were conducted,evidence was evaluated and synthesised,and review criteria and methods were established.Using convenience sampling,39 nurses and 75 indwelling catheterised patients in the General ICU(North Campus) of Wuxi Second People's Hospital, Wuxi, Jiangsu Province, China were selected for baseline review between April and May 2025.Barriers were analysed and change strategies developed based on baseline findings. Results A total of 22 pieces of evidence on urinary leakage prevention and management for ICU patients with indwelling urinary catheters were introduced,leading to the formulation of 21 review indicators. And among those,16 showed that compliance rate was less than 60%. There were 27 barriers and 17 facilitators found by analysis. 25 change strategies were made according to this. Conclusion There are big differences between what we know from research about how to stop or deal with urine leaking in intensive care patients who have a tube in their bladder and what doctors and nurses do in hospitals right now. We need special sets of rules called “evidence-based practice protocols” that use tricks from studies to help doctors and nurses give better care to sick people in the hospital.